2016
DOI: 10.1016/j.chaos.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a common generalized synchronization manifold in network motifs of structurally different time-delay systems

Abstract: We point out the existence of a transition from partial to global generalized synchronization (GS) in symmetrically coupled structurally different time-delay systems of different orders using the auxiliary system approach and the mutual false nearest neighbor method. The present authors have recently reported that there exists a common GS manifold even in an ensemble of structurally nonidentical scalar time-delay systems with different fractal dimensions and shown that GS occurs simultaneously with phase synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Recently, RQA has proved to be useful in diverse areas, such as economy, physiology, earth sciences, astrophysics, and engineering [10,22]. In particular, RQA has been used to investigate complex synchronization scenarios between coupled chaotic oscillators [24], emergence of GS in networks of structurally different timedelay systems [25,26], and precursors and synchronization of components of the tectonic system [27], among others. The oscillatory nature of diverse hydroclimate phenomena is wellknown, such as those associated with the annual cycle of insolation (12 months), and the quasi-periodic El Niño-Southern Oscillation (3-4 years), which constitutes the most important modulator of interannual climate variability worldwide [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RQA has proved to be useful in diverse areas, such as economy, physiology, earth sciences, astrophysics, and engineering [10,22]. In particular, RQA has been used to investigate complex synchronization scenarios between coupled chaotic oscillators [24], emergence of GS in networks of structurally different timedelay systems [25,26], and precursors and synchronization of components of the tectonic system [27], among others. The oscillatory nature of diverse hydroclimate phenomena is wellknown, such as those associated with the annual cycle of insolation (12 months), and the quasi-periodic El Niño-Southern Oscillation (3-4 years), which constitutes the most important modulator of interannual climate variability worldwide [28].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly less attention was paid to synchronization in network motifs of coupled oscillators. In this respect, it is worth mentioning interesting studies with Rössler [Kapitaniak et al, 2015], Rulkov [Sausedo-Solorio and Pisarchik, 2017;Pisarchik et al, 2019], Stuart-Landau [Karakaya et al, 2019], Hodgkin-Huxley [Mirasso et al, 2017], and other models [Suresh et al, 2016]. Concerning Duffing oscillators, we have to mention the paper of Jaros et al [Jaros et al, 2016], who observed different bifurcation scenarios with respect to the coupling strength in three unidirectionally coupled Duffing oscillators. In this paper, we study dynamics of simplest network motifs formed by three Duffing oscillators.…”
Section: Introductionmentioning
confidence: 87%